Internal Migration Patterns in Sri Lanka in 1981 and 1994: A scenario depicting female dominance - Ukwatta, S. (My University, 2003)
This study examines the internal migration patterns and trends of females in Sri Lanka in 1981 and 1994 and identifies popular destinations of female migrants in 1994 and their streams. It also investigates into the demographic and socio-economic characteristics of the female migrants in the identified areas, determinants and possible consequences of migration and highlights the link between the improvement in socio-economic status of women and internal migration. Place of birth method was used to identify the migrants using data from the 1981 Population of Census and Housing and the 1994 Demographic Survey. Appropriateness of the 1994 survey data for migration analysis was studied in detail and the 1981 census data set was adjusted accordingly. Percentage of male lifetime migrants to the Sri Lanka born male population had decreased marginally while the percentage of female lifetime migrants to the Sri Lanka born female population had increased significantly. Colombo, Gampaha, Puttalam, Anuradhapura, Polonnaruwa and Moneragala districts have been designated as the six popular destinations of female migrants in 1994 and their major streams of migration have been identified. Movements of the females in the six popular migrant destinations are much prominent in the labour force age groups. One tenth of the female migrants are the heads of the households. Majority of the female migrants are currently married. The incidence of marriage dissolution is higher among the in-migrants than non-migrants. The general level of education of migrants is higher than the non-migrants. Labour force participation of the in-migrants is more than that of the non-migrants. Majority of the female migrants are engaged in agriculture, manufacturing and elementary occupations. Large proportion of females migrated for employment and the possible positive and negative consequences of such behaviour have been examined. As women constitute a significantly large portion of internal migrants, more data has to be collected on the determinants and consequences of migration and more research has to be done on internal migration focusing on the interrelation between internal migration of females and the improvement of their socio-economic status.